2016
DOI: 10.1002/anie.201510641
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Interfacial Halogen Bonding

Abstract: A homologous series of donor-π-acceptor dyes was synthesized, differing only in the identity of the halogen substituents about the triphenylamine (TPA; donor) portion of each molecule. Each Dye-X (X=F, Cl, Br, and I) was immobilized on a TiO2 surface to investigate how the halogen substituents affect the reaction between the light-induced charge-separated state, TiO2 (e(-) )/Dye-X(+) , with iodide in solution. Transient absorption spectroscopy showed progressively faster reactivity towards nucleophilic iodide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 46 publications
3
44
1
2
Order By: Relevance
“…[45][46][47] The method is described in the experimental section of the Supporting Information whereas the processed data are tabulated in Table 3. [45][46][47] The method is described in the experimental section of the Supporting Information whereas the processed data are tabulated in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47] The method is described in the experimental section of the Supporting Information whereas the processed data are tabulated in Table 3. [45][46][47] The method is described in the experimental section of the Supporting Information whereas the processed data are tabulated in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently,w ei mplemented nanosecondl aser flash photolysis measurements to study the interfacial charge-transfer reactions between the photo-oxidized dye molecules (D + )a nd the charged titania or the cobalt species in the electrolyte. [45][46][47] The method is described in the experimental section of the Supporting Information whereas the processed data are tabulated in Table 3. Figure 6a-c shows that all three electrochemically oxidized dye molecules on titania feature strong electron- ic absorptions in the near-infraredr egion.W ei nitially used ad ye-grafted titania film in contact with acetonitrile to acquire time constants (t 1/2 )o natime scale of millisecond (Figure 6d-f), which were connected with the back-electron transfer from the negatively chargedt itania to D + .W et hen investigated C294 with variousc obalt-based electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a recent study by Swords et al . revealed that an oxidized dye cation ([Dye‐X] + , X = F, Cl, Br, I) with a more polarizable halogen substituent (polarization: F < Cl < Br < I) on the phenyl ring of the triphenyl amine donor shows progressively higher reactivity toward iodide ion and therefore the corresponding DSSC has higher efficiency.…”
Section: Application Of the Resonance Structures To Describe The Dye mentioning
confidence: 99%
“…Sein Forschungsprogramm umfasst Solarzellen, Solartreibstoffe, Energiespeicherung und Katalyse. In der Angewandten Chemie hat er über Halogenbrückenbindungen an Grenzflächen berichtet …”
Section: Ausgezeichnet …unclassified